EFEKTIVITAS TEKNIK MODELING SEBAGAI UPAYA DALAM MENINGKATKAN PERILAKU ASERTIF PADA SISWA KELAS X DI MAS ULUMUL QUR’AN BANDA ACEH - hadisatul mahya; Wanty Khaira (IKIP Siliwangi, 2026)
Assertive behavior is an important social skill that helps students express their opinions, feelings, and needs appropriately without neglecting the rights of others. However, preliminary observations showed that some students still had difficulties expressing their opinions and defending their rights confidently. This study aimed to determine the effectiveness of modeling techniques in improving the assertive behavior of grade X students at MAS Ulumul Qur’an Banda Aceh. The study employed a quantitative approach with a one-group pretest-posttest pre-experimental design. The participants consisted of seven students selected through purposive sampling. Data were collected using an assertive behavior questionnaire and analyzed through descriptive statistics, N-Gain, and paired sample t-test. The results showed that the mean assertive behavior score increased from 46,42 in the pretest to 87,68 in the posttest. The paired sample t-test yielded a significance value of 0,000 (<0,05), while the N-Gain score of 0,7564 (75,64%) was categorized as effective. Therefore, modeling techniques were found to be effective in improving students’ assertive behavior